1987
DOI: 10.1126/science.236.4798.162
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Hazards on the Cascadia Subduction Zone

Abstract: Large subduction earthquakes on the Cascadia subduction zone pose a potential seismic hazard. Very young oceanic lithosphere (10 million years old) is being subducted beneath North America at a rate of approximately 4 centimeters per year. The Cascadia subduction zone shares many characteristics with subduction zones in southern Chile, southwestern Japan, and Colombia, where comparably young oceanic lithosphere is also subducting. Very large subduction earthquakes, ranging in energy magnitude (M(w)) between 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 20 publications
3
94
0
Order By: Relevance
“…Its seismicity is mostly located offshore: along the Mendocino Transform Fault (MTF), within the highly deformed Gorda plate, and along the Cascadia Subduction Zone (CSZ) (Figure 1). Paleoseismic evidence of great earthquakes along the CSZ [Atwater, 1987], including radiocarbon dating and several offshore turbidite episodes of deformation in the last 2000 years [Clarke and Carver, 1992], indicate that the CSZ is capable of multiple M8+ earthquakes, as large as M9 [Goldfinger et al, 2008;Satake et al, 1996;Heaton and Hartzell, 1987].…”
Section: Methodsmentioning
confidence: 99%
“…Its seismicity is mostly located offshore: along the Mendocino Transform Fault (MTF), within the highly deformed Gorda plate, and along the Cascadia Subduction Zone (CSZ) (Figure 1). Paleoseismic evidence of great earthquakes along the CSZ [Atwater, 1987], including radiocarbon dating and several offshore turbidite episodes of deformation in the last 2000 years [Clarke and Carver, 1992], indicate that the CSZ is capable of multiple M8+ earthquakes, as large as M9 [Goldfinger et al, 2008;Satake et al, 1996;Heaton and Hartzell, 1987].…”
Section: Methodsmentioning
confidence: 99%
“…Although the Cascadia subduction zone has many characteristics of the Chilean-type subduction zone, there are some differences [Spence, 1989], the most important being the absence of historic large earthquakes [Heaton and Hartzell, 1987]. Two possible interpretations of this absence are that subduction is occurring aseismically or that elastic strain is The most common method of estimating long-term uplift rates on a tectonically active coast utilizes accurate elevation measurements and dating of late Pleistocene marine terraces.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been cited (Heaton et al, 1987) that suggests that the Cascadia subduction zone has characteristics found in other subduction zones that have experienced large shallow earthquakes. Examples are subduction zones in southern Chile, southwestern Japan and Columbia.…”
Section: Historical Earthquakesmentioning
confidence: 99%